IMPLEMENTASI PERATURAN DAERAH KOTA PEKANBARU NOMOR 5 TAHUN 2002 TENTANG KETERTIBAN UMUM DI KOTA PEKANBARU (STUDI KASUS TERTIB JALAN) - Fitriana Putri Rahayu; Nur Laila Meilani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The population of Pekanbaru has increasingly in every year that resulted in moral of degradation. Moral of degradation is the degradation of a quality in public order. Public order is a condition that support for the government and people's activities in implementing development in a region. It can be happend by various causes and circumstances, for an example violation of law which still happened in Pekanbaru. The violation of law that usually happend is violation of traffic signs. The purpose of the study to analyze the implementation and know the factors that affect of regional regulation in Pekanbaru city no. 5 of 2002 on public order in Pekanbaru (study case of the street orderly). The concept of this research is the implementation policy theory by Ripley and Franklin in Tahir (2015: 95). It is about the success of the implementation policy based on 3 perspectives such as : The Loyalty of Bureaucracy Level (Compliance), have a Smooth Routine and there is no problem, the last is Performance. This research design of this study case which use qualitative approach . The results of this study is the Implementation of Regional Regulation in Pekanbaru has not been implemented optimally . It is because The Loyalty of Bureaucracy Level that has not been implemented in good way that we can see some of people’s still ignored the regulation of road rules from government. As a result, the routines by the implementor have an insufficient that impact on staff performance. The factors that influence the implementation of the local regulation is the lack of awareness of the implementors and the lack of supervision from the implementors which causes problems on public policy, especially the road rules policy has been implemented yet optimally in the city of Pekanbaru.Keywords: Public Order, Policy Implementation, The Street Orderly